Aspectos econômicos e sociais do complexo agronegócio cavalo no estado de Minas Gerais - Elvia Rocha Vieira (2011)
The present study has characterized the horse breeding and related activities in the state of Minas Gerais. The state was divided in 7 extracts in what 967 interviews were performed in rural properties and in the main equestrian events in 2010. The activity of governmental organizations in the horse breeding and the involvement of the state in international trade of horses and horse meat were also investigated. Data obtained were analyzed by descriptive statistics, correlation, regression and analysis of variance considering a 5% rate of type I error. The study demonstrated that nurseries in Minas Gerais have, in mean, 18 years and 2 months, and in 49.95% of them horses are created for help in agricultural activity. It was also observed that although the state has the biggest horse herd in Brazil, the herd in Minas Gerais has been reduced. Although there is an intimate relation between horse and cattle distribution in Minas Gerais, the correlation between the rates of growth of both bunches is negative. The walker breeds are the majority in Minas, and they are responsible by the large number of equestrian events in the state. The increased number of equestrian events in Minas indicates that the use of horses in leisure and amateur and professional sportive activities is expanding. In 16.57% of the nurseries, horses are breeding for leisure, and only at 6.8% of them horse breeding is focused exclusively in trade. The estimated annual spent with horse breeding in Minas Gerais is of R$468.907.276,21. According to most of the breeders (85.23%) the main barriers in horse breeding include market and the costs of breeding, the great supply of animals and unfair concurrency, costs and qualification of the workforce, scarcity of public policies and sanitary and nutritional management. In 2009 Minas Gerais was responsible for 39.18% of the horse meat exported by Brazil, although the export of animals is still incipient. This pioneer study demonstrated that horse breeding needs more attention from public and private sectors to be consolidated as an expressive activity in the economy of Minas Gerais